Combined incubation of cadmium, docosahexaenoic and eicosapentaenoic acid affecting the oxidative stress and antioxidant response in human hepatocytes in vitro - Linhartova, P; Gazo, I; Sampels, S (Physiological research, 2016)
Human hepatocellular cells Hep G2 were used to investigate the effects of the intake of contaminated fish on oxidative stress. Uptake of heavy metal contaminated fish was mimicked by incubating the cells with a combination of cadmium chloride (Cd(2+)) as possible contaminant and a combination of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) as important fatty acids (FA) specific for fish. The main aim of this study was to determine the effects of these co-incubations (FA, Cd(2+)) on lipid and protein oxidation. In addition we also evaluated the antioxidant response of the cells using two different methods (SOD and TAC). Pre-incubation with the chosen FA significantly reduced the oxidative stress caused by incubation with Cd(2+). We measured an increased level of carbonyl proteins (CP) in the cells pre-incubated with bovine serum albumin (BSA) and post-incubated with Cd(2+).
Keywords: hepatocyty; Docosahexaenoic Acids; Hepatocytes; Oxidative Stress; kyselina eikosapentaenová; chlorid kademnatý; Hep G2 Cells; lidé; Antioxidants; buňky Hep G2; Cadmium Chloride; oxidační stres; Eicosapentaenoic Acid; antioxidancia; kyseliny dokosahexaenové; Humans